In neurons, activity-dependent association of dendritically transported mRNA transcripts with the transacting factor CBF-A is mediated by A2RE/RTS elements - Raju, Chandrasekhar S. (The American Society for Cell Biology, 2011)
In neurons certain mRNA transcripts are transported to synapses through mechanisms that are not fully understood. Here we report that the heterogeneous nuclear ribonucleoprotein CBF-A (CArG Box binding Factor A) facilitates dendritic transport and localization of activity-regulated cytoskeleton-associated protein (Arc), brain-derived neurotrophic factor (BDNF), and calmodulin-dependent protein kinase II (CaMKIIα) mRNAs. We discovered that, in the adult mouse brain, CBF-A has a broad distribution. In the nucleus, CBF-A was found at active transcription sites and interchromosomal spaces and close to nuclear pores. In the cytoplasm, CBF-A localized to dendrites as well as pre- and postsynaptic sites. CBF-A was found in synaptosomal fractions, associated with Arc, BDNF, and CaMKIIα mRNAs. Electrophoretic mobility shift assays demonstrated a direct interaction mediated via their hnRNP A2 response element (A2RE)/RNA trafficking sequence (RTS) elements located in the 3′ untranslated regions. In situ hybridization and microscopy on live hippocampal neurons showed that CBF-A is in dynamic granules containing Arc, BDNF, and CaMKIIα mRNAs. N-methyl-d-aspartate (NMDA) and α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate (AMPA) postsynaptic receptor stimulation led to CBF-A accumulation in dendrites; increased Arc, BDNF, and CaMKIIα mRNA levels; and increased amounts of transcripts coprecipitating with CBF-A. Finally, CBF-A gene knockdown led to decreased mRNA levels. We propose that CBF-A cotranscriptionally binds RTSs in Arc, BDNF, and CaMKIIα mRNAs and follows the transcripts from genes to dendrites, promoting activity-dependent nuclear sorting of transport-competent mRNAs.